EXAMINING THE EFFECT OF AUDIT RISK, OPERATIONAL COMPLEXITY, AND INTERNAL CONTROL SYSTEMS ON AUDIT QUALITY - Sigit Sukmono (International Journal Management and Economic, 2026)
This study aims to examine the effects of audit risk, operational complexity, and internal control systems on audit quality. High audit risk and increasingly complex business operations present significant challenges for auditors in obtaining sufficient and appropriate audit evidence, while effective internal control systems are expected to improve the reliability of financial reporting and support higher-quality audit outcomes. A quantitative research approach with an explanatory design was employed. Secondary data were collected from annual reports and audited financial statements of companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using purposive sampling based on predetermined criteria. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The findings indicate that audit risk has a significant negative effect on audit quality, suggesting that higher audit risk increases the likelihood of material misstatements and reduces audit effectiveness. Operational complexity also has a significant negative effect on audit quality because diversified business activities require broader audit procedures and greater professional judgment. Conversely, internal control systems have a significant positive effect on audit quality by improving the reliability of financial information and reducing control risk. Furthermore, audit risk, operational complexity, and internal control systems simultaneously have a significant influence on audit quality. These findings highlight the importance of comprehensive risk assessment, effective internal control implementation, and appropriate audit planning in enhancing audit quality. The study contributes to the auditing literature by providing empirical evidence regarding the combined effects of organizational and audit-related factors on audit quality in publicly listed companies.